Experiencing Leadership Like a Coach - Matthews, Nancy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
This note is a reflection on experiences as an educational leader, as well as provides a perspective on educational leadership, based on professional reading. It offers the metaphor of the coach, initiating a case for using a coaching philosophy as a model for a sustained form of leadership. It invites the reader to consider that with a game plan and a coaching mindset, a school can reach its full potential.